Studi Formasi Sosial pada Industri Kecil Agro di Priangan Timur - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Universitas Galuh, 2024)
Agro-small industry entrepreneurs as a social group are integrated into a social structure. In sociological studies, the presence of this group of entrepreneurs also shows their social structure. To better understand the social reality of entrepreneurs in carrying out their production processes, the concept of Production Mode is known. This research aims to explore the production modes that occur in the next generation of small agro industries in East Priangan. Using a qualitative approach, data was collected by interviewing four owners of the next generation of small agro industries who have survived across generations. Thematic analysis with N-vivo version 12 software was used to analyze the data obtained. This research reveals that there is more than one mode of production that coexists in agro-small industries in East Priangan, so the concept of social formation is more appropriate to use. The social formations most commonly found in the third generation are